DETERMINAN YANG MEMPENGARUHI KEMISKINAN DI PULAU JAWA (PERSPEKTIF TEORI PRO-POOR GROWTH & HUMAN CAPITAL) - Fauziah, Nurafikatul; Agus Suman (Journal of Development Economic and Social Studies, 2024)
Despite being the economic and governmental center, the number of impoverished people in Java Island exceeds half of the total impoverished population in Indonesia. Based on this, this research aims to examine the determinants influencing poverty in Java Island, covering 6 provinces during the period 2015-2022, based on the perspectives of pro-poor growth theory and human capital. The data used is sourced from BPS and employs panel data analysis techniques with a fixed-effect model. The research findings indicate that, individually, education and unemployment do not have a significant impact on poverty. Meanwhile, economic growth and the Human Development Index (HDI) have a negative and significant impact on poverty in Java Island. Simultaneously, economic growth, education, HDI, and unemployment collectively influence poverty in Java Island.